Studi Komparatif Penerapan Pendekatan Universal Design: Studi Kasus: Masjid Al Mujahidin Bandar Lampung, Masjid Baitus Shobur Tulang Bawang Bawat, dan Masjid Sudalmiyah Rais Surakarta - Putri Anjani; Suci Lestari (Arsir: Jurnal Arsitektur, 2026)
Mosques serve not only as places of worship but also as centers of social activity for Muslim communities. However, many mosques in Indonesia still fall short in meeting accessibility standards for vulnerable groups such as the elderly, persons with disabilities, and individuals with special needs. According to Statistics Indonesia (BPS, 2022), there are more than 22 million people with disabilities in the country. This study highlights the importance of applying the Universal Design concept in mosque architecture to create inclusive, safe, and comfortable worship spaces for all. Referring to the seven principles of Universal Design, the study evaluates their implementation in three mosques in Indonesia—Al Mujahidin Mosque in Bandar Lampung, Baitus Shobur Mosque in Tulang Bawang Barat, and Sudalmiyah Rais Mosque in Surakarta. Using a qualitative descriptive method and comparative analysis, this research reveals the strengths, weaknesses, and challenges in realizing mosque designs that are accessible to everyone. The findings aim to serve as a foundation for developing more inclusive mosques in the future. Keywords: Mosque, Universal Design, accessibility, inclusive architecture, disability.